Transport of yttrium metal ions through fibers supported liquid membrane solvent extraction - Gaikwad, Abaji G.; Rajput, A. M. (Journal of Rare Earths, 2010)
A novel idea of transport of yttrium (III) metal ions through fibers supported liquid membrane in two stage processes namely source to membrane and membrane to receiving phase has been proposed. The fibers supported liquid membrane was impregnated with different concentrations carrier. The experimental variables explored were concentration of yttrium (III) ions, pH of source phase, PC-88A concentration in membrane phase, acid concentration in receiving phase and stirring speed. The pre-concentration of yttrium MO ions was investigated from the dilute solutions. The two-channel fibers supported liquid membrane solvent extraction was investigated for the transport of yttrium (III) ions from the source to membrane and membrane to receiving phase. The transport of yttrium (III) ions was observed through the fibers supported liquid membrane with capillary action.
Keywords: channel; extraction; fibers supported liquid membrane solvent extraction; PC-88A; rare earths; stripping; yttrium metal ion